No effect of upper body compression garments in elite flat-water kayakers - Dascombe, B.; Laursen, P.; Nosaka, K.; Polglaze, T. (European Journal of Sport Science, 2013)
While the effect of lower body compression garments on performance and physiological responses are well documented, no studies have examined the effect of upper body compression garments (UBCG) on upper-body dominant exercise. This study examined the effects of wearing UBCG on performance and physiological responses during simulated flat-water kayaking. Five male (mean values±s: 21.8±2.8 years; 83.5±9.2 kg; 63.0±5.5 ml/kg·min) and two female (mean values±s: 25.0±4.2 years; 71.4±2.7 kg; 51.0±4.8 ml/kg·min) elite flat-water kayakers completed a six-step incremental test followed by a four-minute maximal performance test (4minPT) in both UBCG and control (no shirt or sports training bra) conditions in a randomized counter-balanced order. Heart rate and oxygen consumption (O2) as well as performance measures (power, distance covered, stroke rate) were recorded during the tests, and blood lactate was measured immediately after each incremental step and three minutes following the 4minPT. Near-infrared spectroscopy-derived measures of blood flow and oxygenation of the flexor carpi radialis were monitored continuously for all tests. No significant differences between the UBCG and control conditions were evident for any performance, cardiorespiratory or oxygenation measure across the incremental step test and 4minPT. It was concluded that wearing UBCG did not provide any significant physiological or performance benefits during simulated flat-water kayaking.